Effects of self-monitoring of blood glucose on diabetes control in a resource-limited diabetic clinic. Issue 2 (15th July 2016) - Pillay, S; Aldous, C
Abstract : Background: Diabetes mellitus places an enormous burden upon both patients and countries' health systems. Integral to achieving control is patients assuming responsibility for their condition. Self-monitoring of blood glucose (SMBG) can serve as a powerful tool modifying lifestyle behaviour and can aid in achieving optimal control. Methods: This study assessed the effect on diabetes control in patients who received glucometers and education over 12 months. This data was analysed at baseline, 6 and 12 months. Results: Glycaemic control improved significantly between baseline, 6 and 12 months (HbA1c% 12.29 ± 3.17 vs. 11.16 ± 3.09 vs.±10.68 ± 3.10, respectively). The number of patients achieving target glycaemic control increased substantially while the number of patients achieving target total cholesterol and triglyceride levels improved at six months. Mean HDL cholesterol increased significantly between baseline and 12 months (1.20 ± 0.42 vs. 1.31 ± 0.40, respectively; p -value 0.0095). The mean BMI of male patients in the study increased between 6 and 121 months (27.59 ± 6.42 vs. 31.90 ± 8.85, respectively, p  = 0.0012) and between baseline and 12 months (27.64 ± 6.13 vs. 31.90 ± 8.85, respectively, p  = 0.0012). Conclusion: This study demonstrated that the introduction of SMBG and patient education, within this resource-limited clinic setting, had beneficial effects on diabetes control; however, obesity remains an obstacle to optimal control.